Information Seeking Behavior Through Media About “The 2014 Indonesian Presidential Election” - Eni Maryani, Eni Maryani; Kismiyati El Karimah, Kismiyati El Karimah (2015)
Presidential election is an important process in Indonesia as the democratic country. The democratic process requires people’s participation. The quantity and quality participation of voters are assumed closely related to their political consciousness. This study aim to explore the media used in Indonesian presidential election, the diversity of information, the credibility of resources gained and also the information process and evaluation by the voters. The method used is qualitative with interviews, observation and focus group discussion as data collection techniques. The subject of the research is first-time voters in the 2014 Indonesian presidential election.